2019
DOI: 10.1097/ico.0000000000002043
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Best-Corrected Visual Acuity With Swept-Source Optical Coherence Tomography Parameters in Keratoconus

Abstract: Purpose: This study aimed to predict the best-corrected visual acuity (BCVA) based on swept-source optical coherence tomography (SS-OCT) parameters in eyes with keratoconus. Methods: We retrospectively reviewed 135 eyes of 135 patients with keratoconus (mean age: 31.9 ± 12.4 years). The average keratometry value and BCVA (logarithm of the minimal angle of resolution [Snellen]) were 48.68 ± 5.44 diopter and 0.20 ± 0.36 (20/25), respectively. Eleven param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…According to previous authors 21 , 22 , Kmax was the topographic parameter that explains the highest percentage of visual acuity. MCT was found to be a useful parameter for early diagnosis and progression of keratoconus patients.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…According to previous authors 21 , 22 , Kmax was the topographic parameter that explains the highest percentage of visual acuity. MCT was found to be a useful parameter for early diagnosis and progression of keratoconus patients.…”
Section: Discussionmentioning
confidence: 77%
“…Total RMS and vertical coma correlated better with loss of vision. Esaka et al 22 found that RMS of corneal elevation (RMSE) (r = 0.699) and total coma aberration (r = − 0.513) were related with BSCVA (logMAR). In our study, correlations were found among V.L.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations